Seasonal Impact on the Demand of Finished Products of Sualkuchi Silk Industries: Application of Dummy Variable Technique - Debtosh Chakraborty (Research Parks Publishers, 2021)
Very often a year is divided into several seasons with respect to the demand of certain product. This study laid emphasis on the demand of Mulberry Silk product of Sualkuchi silk industries and Dummy Variable Technique is used to to test the effect of seasonal fluctuation on the demand of Mulberry Silk Product.